Early literacy with augmented reality - Olena Ie. Piatykop; Olha I. Pronina; Iryna B. Tymofieieva; Ihor D. Palii (Academy of Cognitive and Natural Sciences, 2022)
Augmented reality is currently one of the most rapidly emerging technologies, with applications in the field of education. AR technology, according to a review of numerous publications, provides new options for teachers and makes learning more appealing to pupils of all ages. Students can use mobile AR apps to observe a real-world environment with virtual things layered or composited on top of it. This is especially true for young children. The article highlights the activities that allow a child to have a unique AR experience. There is a comparison of available augmented reality (AR) applications for learning the alphabet. The author describes a novel augmented reality application that was created with Unity, C#, and Vuforia. The developed mobile AR application allows students to learn the Ukrainian alphabet, number names, and animal sounds. The learning process is enhanced by three-dimensional visualization and sounding of each letter and number thanks to this program. An analysis of a survey of teachers and parents found that utilizing an AR application greatly boosted children's motivation and self-efficacy in learning letters and numbers. The AR application aided in the retention of the child's attention while learning new content by speeding up the process of memorization.